Vertigo following cochlear implantation: a review - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2022)
Cochlear implantation may cause a detrimental effect on vestibular function and residual hearing. A significant number of patients with a cochlear implant present with vertigo. There are several mechanisms for dizziness following cochlear implantations. The causes may be surgical trauma, disruption of normal cochlear physiology, or ensuing endolymphatic hydrops. Vibratory trauma affecting the cochlea during cochleostomy plays a vital role in causing paroxysmal vertigo in patients with a cochlear implant. In addition, the vibrations affecting the cochlea are enough to dislodge otoconia particles. During cochlear implantation, it is necessary to insert an electrode array into the cochlea and thus the chance of damage to cochlear and function may happen. Dizziness or vertigo may develop after cochlear implantation. It usually occurs due to vestibular hypofunction. Vertigo following cochlear implantation has not frequently been documented in the literature previously. However, the increasing number of cochlear implantations in the current scenario is showing different postoperative complications like vestibular symptoms among patients with an implant. The vestibular symptoms following cochlear implantation range from a gradual sense of mild unsteadiness or lightheadedness to brief attacks of whirling vertigo. Vertigo following cochlear implantations affects the quality of life although vestibular therapy is often helpful to manage this condition. The article aims to provide a comprehensive review of vertigo following cochlear implantation.